WOMEN AND MORALITY IN CHURCH AND STATE RELATION: Feminist Perspectives on the Vatican Discourse in International Politics - Orate, Allan C. (Philippine Journal of Social Development, 2010)
Religion, ethics and gender have been historically displaced by statecetric discourse of realism in international relations.  Postmodern and critical  feminist critique of the realist paradigm foregrounds issues of gender and religious morality. The Vatican-State with the pope, represented by the Holy See, has privileged the moral voice of  the Catholic church in world politics. In international conferences on women, the church has rendered ethical perspective to various issues according to the view that natural law is the basis of international consensus.  By universalizing and essentializing moral principles, the Vatican has marginalized the liberating voices of women in world affairs. Criticizing the church’s moral point of view from feminist standpoints reveals gender bias against women. The church’s politics of a morality has not actually liberated women from oppression, rather it has preserved patriarchy and has promoted the subordination of women under men by maintaining the hierarchical structure of the institutional church. The church constructs women along the domestic role of mothering and caring, thereby hindering their liberation by justifying their subjugation through moral theologizing.  The best that both the church and the state could do to women is to help them determine themselves by personal choices rather than control them to conform to the instituted power in the international society.